Struktur Puisi Karya Defri N Sae dalam Kumpulan Puisi " Atas Nama Cinta dan Benci" serta Relevansinya dalam Pembelajaran Sastra di SMP - Imaniah Kusuma Rahayu; Alfonsia Erlinda Meas; Marnina Silla (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the structure of poetry by Defri N Sae in the collection of poems "In the Name of Love and Hate" and its relevance in learning literature in junior high school. The data of this research are in the form of words, quotes, and sentences in the collection of poems. The data source for this research is a collection of Poems in the Name of Love and Hate by the Yususf GMKI Kefamenanu Commissariat which was published in 2021 by the publisher Ruang Pustaka. The method used is descriptive qualitative. From the results of research on 8 poems by Defri N Sae, these poems can be used as teaching materials, because the building elements contained in the poems are quite complete. The building elements consist of diction, imagery, concrete words, figure of speech, levers, typography, theme, tone, feeling, and message. KD: 3.7 Identify the building blocks of the poetry text that is heard or read and KD 4.7 Identifying the building blocks of the poetry text summarizing the builidng blocks and the meaning of the poetry text that is heard or read Both KD require students to be able to identify and conclude the building blocks and meanings of the text they hear or read. Based on the level of difficulty, Defri N Sae's poem is not that difficult and describes a place on the island of Timor. This of course makes it easier for readers to understand this because of its contextual nature so that it is worthy of being used as learning material at the junior high school level. Keywords: Structure of poetry, Literature Learning, Junior High School